Study on water and soil quality source apportionment of pollution loading and community engagement for integrated catchment management of Gebeng Industrial Estate, Pahang, Malaysia - Gabar, Salah Masoud Saleh Gabar (2019)
A study was carried out to evaluate the surface water and soil quality, source apportionment of pollution loading of the Gebeng industrial area and local participant to propose a model for integrated catchment management of the area. Water samples were collected from the surface water of the Tunggak and Balok rivers for a period from October 2016 to August 2017 from 10 sampling stations. Soil samples were also collected from 10 stations two times in the dry and wet season. A total of 15 water parameters with ten heavy metals, and soil properties with ten heavy metals were analysed according to the standard method procedures. Data analysis was conducted using SPSS 21.0 statistical software. Of all the 25 water quality parameters, 16 parameters were found to be beyond the recommendation of the (EQR) Malaysia. The concentration of pH was in acidity range (6.61) and DO were very low (4.39 mg/L) over the whole area. Accordingly, TDS, TSS, EC, BOD, COD, AN, TP, O&G, Cd, Co, Cu, Pb, Mn, and Ni were observed in higher concentration due to industrial wastewater. The overall results of DOE-WQI revealed that the surface water of the Gebeng area was classified under class III. The results of soil properties indicated that lower soil pH, OM, and EC and most of the particle size of the Gebeng area soils were silt and clay. The soil pollutants were assessed by ecological risk index such as geo-accumulation index (Igeo), contamination factor (CF), and pollution load index (PLI). The soil Igeo and CF revealed that the industrial zone was contaminated by five heavy metals which are: As, Cd, Co, Cu, and Pb. The overall of PLI at the industrial zone stations was greater than 1, which indicated that there is soil heavy metals pollution at industrial zone. Source apportionment study for surface water and soil parameters revealed that the significant sources of pollution were due to anthropogenic activities. The sources of water pollution were primarily due to the industrial effluents associated with domestic wastewater, agriculture and urban runoffs in addition to the natural sources. Two types of the survey were distributed to three different groups. Knowledge, Attitude, and Practices survey (KAPS) was distributed on local community people and industries employees to know the knowledge, attitude, and practices of these people about industrial pollution issue. A general survey was distributed to authorities (DOE) to understand their willingness to participate in a collaborative effort with the local community people and industries employees. Demographics characteristics of the local community and industries employees showed that older people, people with higher education level, old residents, years of work experience were the most important people who observe the change of the surface water and soil quality. A total score of KAP survey results revealed that local people have good knowledge, attitude, and practices to the issue, whereas the industries employees have good knowledge, attitude, and bad practices. All three different groups were excited to participate in a collaborative effort for protecting the area from contamination. Consequently, combined the results of the scientific findings with local community and industries employees survey showed significant associations and gave the final visualization for suggested integrated catchment management (Environmental Control Program ECP) model.